Modern art and stage costume: The case of Dragilev's Ballets Russes - Frfulanović Dragana; Jevtović Aleksandra; Savić Milena (Tekstilna industrija, 2022)
Sergei Dragilev recognized the vitality of modern art that brought freshness to the culture, so all innovative artists of the time were invited to join his campaign and goal. And he reflected on the fact that ballet breaks the shackles of the traditional concept in the performance of dance, music, costume design, and scenography and imposes an element of challenge by introducing current contemporary tendencies in art and culture. All the famous names of the art of that time brought the latest achievements of modern art into the world of dance: Pablo Picasso, Natalia Goncharova, Henri Matisse, and Giorgio de Chirico. And with them, the design of scenography and costume design took the form of cubism, fauvism, futurism, surrealism, and other avant-garde movements, while refreshing the themes, which overall influenced ballet to become part of popular culture.